2022
DOI: 10.3390/ijms23136935
|View full text |Cite
|
Sign up to set email alerts
|

Seventy-Two-Hour LRRK2 Kinase Activity Inhibition Increases Lysosomal GBA Expression in H4, a Human Neuroglioma Cell Line

Abstract: Mutations in LRRK2 and GBA1 are key contributors to genetic risk of developing Parkinson’s disease (PD). To investigate how LRRK2 kinase activity interacts with GBA and contributes to lysosomal dysfunctions associated with the pathology of PD. The activity of the lysosomal enzyme β-Glucocerebrosidase (GCase) was assessed in a human neuroglioma cell model treated with two selective inhibitors of LRKK2 kinase activity (LRRK2-in-1 and MLi-2) and a GCase irreversible inhibitor, condutirol-beta-epoxide (CBE), under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For their part, Ruz et al [4], in their original research article, analyze the mechanisms involved in the pathogenesis of Parkinson's disease (PD). PD is an age-related chronic neurodegenerative disorder, and decades of research, among other risk factors, have established the importance of rare and common genetic variants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For their part, Ruz et al [4], in their original research article, analyze the mechanisms involved in the pathogenesis of Parkinson's disease (PD). PD is an age-related chronic neurodegenerative disorder, and decades of research, among other risk factors, have established the importance of rare and common genetic variants.…”
mentioning
confidence: 99%
“…Notably, mutations in LRRK2 or GBA1 genes or alterations in their enzymatic activities are well-recognized contributors to PD pathogenesis, but despite this, the specific mechanistic interplay between these two molecules remains undetermined. In this sense, Ruz and colleagues [4] reported that the inhibition of LRRK2 kinase activity in a human neuroglioma cell model resulted in increased GBA protein levels with no changes in the overall GCase activity compared to the control cells. This study suggests a possible regulation of lysosomal function through LRRK2 and supports an interplay between LRRK2 kinase activity and GBA.…”
mentioning
confidence: 99%